Prehistoric Anthropomorphic Figurines of the Ancient Near East and the Aegean. Ph. D. Vol. 1 - Ucko, Peter John (1962)
Typescript; Bibliographie, Typologie und Klassifikation der Figuren in Menschengestalt aus Kreta, Griechenland, Ägypten und Vorderasien. 788-843: Interpretation of the function of prehistoric anthropomorphic figurines “No firm evidence has been found on the basis of any of these figurines for the existence of a deity connected with fertility, nor for the worship of a mother goddess”.